Pengaruh Waktu dan Konsentrasi Enzim A-Amylase dan Glukoamilase pada Hidrolisis Biji Cempedak sebagai Bahan Baku Bioetanol - RA Ghina Sayyidah Achva; Jaksen M. Amin; Anerasari Meidinariasty (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Bioethanol is a renewable energy source with great potential for development in Indonesia. Bioethanol is produced from the fermentation of sugar, starch or lignocellulosic biomass. In addition, cempedak seeds also contain sugars such as glucose, fructose and sucrose, which provide fast energy. The aim of this study is to identify the optimal composition by varying the hydrolysis time and adding alpha-amylase and glucoamylase enzymes. In the pre-treatment process, Cempedak seeds are processed and then the hydrolysis process is continued with variations in the addition of α-amylase and glucoamylase enzymes. (0.5%:1.5%:2.5%) (v/v) and then analysed for sugar content. From the results of the analysis, the highest % Brix was 16% at a hydrolysis time of 70 minutes with an enzyme concentration of 2.5%. The lowest water content of 98.93% was obtained at a hydrolysis time of 70 minutes and an enzyme concentration of 2.5%. In addition, the best sugar content results were used as raw material for bioethanol production and the ethanol content was checked. The fermentation process was carried out for 6 days and the ethanol content obtained was 64.95%, based on analysis by GC-MS.